Potensi dan Strategi Pengembangan Objek Wisata Alam Air Terjun Lae Une di Kabupaten Pakpak Barat - Daulay, Nadia Saputri; Priscillia Febrianty Purba; Banjarnahor, Pretty Grace; Sari Ritonga, Siti Fatimah; Qriah Br Ginting; Lubis, Fitriani (Al-Hayat: Natural Sciences, Health & Environment Journal, 2023)
Lae Une waterfall is a tourist destination located in West Pak-pak. This waterfall is very rarely visited due to the lack of available facilities. A strategy to develop the Lae Une tourist attraction in West Pak-Pak Regency is very necessary. In developing the Lae Une tourist attraction, there needs to be participation and awareness from the community. Through this, this research uses a data analysis method in the form of qualitative descriptive analysis. Researchers as key instruments, with detailed sampling of data sources. This research was carried out by collecting data on a natural background at Lae Une Waterfall with the aim of interpreting the phenomena that occur and providing ways to develop Lae Une Waterfall into a natural tourist destination.